How do location and control over the music influence listeners’ responses? - Krause, Amanda; North, Adrian (Wiley-Blackwell Publishing Ltd., 2017)
This study uses Mehrabian and Russell's () Pleasure-Arousal-Dominance (PAD) model to consider how responses to both the music heard and overall in-situ listening experience are influenced by the listener's degree of control over music selected for a particular listening episode and the location in which the listening takes place. Following recruitment via campus advertisements and a university research participation program, 216 individuals completed a background questionnaire and music listening task in a 3 (location) × 2 (experimenter- or participant-selected music) design. After the listening task, participants completed a short questionnaire concerning the music they heard and the overall in-situ listening experience. Results demonstrated that there was a positive relationship between control and liking for the music and episode, whether the former was considered in terms of: (1) whether the music was self-selected or experimenter-selected or (2) overt ratings of perceived control. Furthermore, the location and liking for the music were related to people's judgments of their enjoyment of the overall experience. This research indicates that the PAD model is a useful framework for understanding everyday music listening and supports the contention that, in a musical context, dominance may be operationalized as control over the music. © 2017 Scandinavian Psychological Associations and John Wiley & Sons Ltd.